Diagnostic approach to catastrophic musculoskeletal injuries in racehorses. (July 2017) - Diab, Santiago S.; Stover, Susan M.; Carvallo, Francisco; Nyaoke, Akinyi C.; Moore, Janet; Hill, Ashley; Arthur, Rick; Uzal, Francisco A.
Catastrophic musculoskeletal injuries are the most common cause of euthanasia or spontaneous death in racehorses, and the most common cause of jockey falls with potential for serious human injury. Horses are predisposed to the vast majority of these injuries by preexisting lesions that can be prevented by early diagnosis and adequate bone injury management. A thorough examination of the musculoskeletal system in racehorses often determines the cause of these injuries and generates data to develop injury prevention strategies. We describe the diagnostic approach to musculoskeletal injury, review the methodology for the examination of racehorse limbs, and provide anatomy and pathology tools to perform an organized and thorough postmortem examination of the musculoskeletal system in equine athletes.